SUSTAINABILITY MEASUREMENT INDICATORS AND CORRELATIONS BETWEEN PERFORMANCE INDICATORS AND SUSTAINABILITY INFORMATION DISCLOSURE: CASES OF LISTED COMPANIES IN VIET NAM (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
Purpose -The article presents indicators to measure the sustainable development of enterprises interms of economy, society and environment; evaluates the correlations between effective factorssuch as ROE, ROA, PE, EPS, market capitalization and the disclosure of information on thesustainable development of enterprises. We aim to provide a theoretical basis for solvingpractical accounting-related problems in larger organizations and society. We also hope tocomplement the purely theoretical research on methods of assessing economic, social andenvironmental impacts. The article presents the essence of applied accounting research that iscontextualized with relevant practical implications and contributes to the theoreticalunderstanding towards sustainable development.